Kecerdasan dalam Pembelajaran Matematika - Jumadi, Jumadi (AKSIOMA : Jurnal Matematika dan Pendidikan Matematika, 2020)
This study aims to analyze the relationship between IQ test results and studentintelligence in learning mathematics through the Multiple Intelligence Theory.This research is a qualitative study which uses primary references forintelligence in mathematics learning and correlates with IQ tests based onmultiple intelligence theory.The results of research that discusses the theory of Multiple Intentions that areable to change the view of intelligence as seen from the results of IQ tests are nolonger relevant because IQ tests only discuss intelligence intelligence,mathematics and language. IQ tests only support math-intelligence andlanguage, while learning mathematics involves not only intelligence andlanguage. If the school wants to implement Multiple Intelligences in itseducation system, then it needs help from each teacher to ask to start and ask toput all his skills and creativity into teaching.Keywords: Multiple intelligence, multiple intelligence, IQ, mathematicalintelligence